2007
DOI: 10.1016/j.top.2006.10.002
|View full text |Cite
|
Sign up to set email alerts
|

On spineless cacti, Deligne’s conjecture and Connes–Kreimer’s Hopf algebra

Abstract: Using a cell model for the little discs operad in terms of spineless cacti we give a minimal common topological operadic formalism for three a priori disparate algebraic structures: (1) a solution to Deligne's conjecture on the Hochschild complex, (2) the Hopf algebra of Connes and Kreimer, and (3) the string topology of Chas and Sullivan.From this description one obtains several useful corollaries [18]. The ones relevant to the present discussion are listed below. Corollary 2.16The quasi-operad of normalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(112 citation statements)
references
References 29 publications
(104 reference statements)
2
110
0
Order By: Relevance
“…We do not wish to go into the gory details. The proof is a straightforward adaption from that of Cacti presented in [Ka1,Ka2]. For the semi-direct product the first homeomorphism is given by reading off the weights at each boundary and then taking the projective class of the weights at each boundary individually.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…We do not wish to go into the gory details. The proof is a straightforward adaption from that of Cacti presented in [Ka1,Ka2]. For the semi-direct product the first homeomorphism is given by reading off the weights at each boundary and then taking the projective class of the weights at each boundary individually.…”
Section: 2mentioning
confidence: 99%
“…This is not surprising, but here we have a very geometric picture. For the actions, we can take the action of the chain operad on itself of the action on the Hochschild complex as defined in [Ka2]. Using the former action, we obtain a universal geometric point of view.…”
Section: Explicit Operationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[Kontsevich has suggested that this is always so, but his program of proof fails, by the arguments of [4], and at present the question seems to be open.] Connes and Kreimer [12, 21, There are deep connections between the Grothendieck -Teichmüller group and the Lie algebras of these automorphism groups [29,54], and it seems likely that they (and the theory of quasisymmetric functions, via free Lie algebras) will eventually be understood to be intimately related; the appearance of polyzeta values in the theory of quantum knot invariants (cf. eg [36]) is another source of recent interest in this subject.…”
Section: 2mentioning
confidence: 99%
“…The CK Hopf algebra also appears in relation to a conjecture of Deligne on the existence of an action of a chain model of the little disks operad on the Hochschild cochains of an associative algebra (cf. Kaufmann [75]). …”
Section: Further Developmentsmentioning
confidence: 99%